EVALUATION OF INDOOR COMFORT AND BUILDING ENERGY PERFORMANCE OF STUDENTS RESIDENCE AT SAM RATULANGI UNIVERSITY IN MANADO, INDONESIA - Sangkertadi Sangkertadi (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2011)
There is no information that the student residence of Sam Ratulangi University is especially designed energy-efficient. It is necessary to evaluate the design from the view point of energy conservation associated with the fulfillment of indoor comfort. Through this study, observation, measurements and calculations of comfort, ventilation, heat and lighting were performed to get information if the design follows the Indonesia standards on comfort and energy conservation. Questionnaires to residents were also conducted to obtain compliance response to the comfort standard. Air temperature, wind speed, humidity and lighting were measured, simultaneously with a questionnaire regarding the level of comfort to occupants. Scale of the thermal comfort in the room refers to the ISO-7748. The use of electronic devices such as computers, fan, TV, etc. are also recorded to determine the level of electrical energy consumption. The results generally indicate that there are differences in comfort perception between the level based on references and by the respondents. Overall, the design is not a type of energy efficient building even OTTV of the building envelope is 49.79 W/m2. Energy consumption of the rooms are in range of34 kWh/m2/year to 157 kWh/m2/year.